Salud mental y el uso excesivo de internet. - Mamani Roque, Maribel; Gómez Quispe, Jhenny Irene; Callohuanca Avalos, Edgar Darío; Trigos Sánchez, Lily Maribel; Fura Vizcarra, Yony Millart; Yucra Quispe, Teófilo (Revista de Investigación en Salud VIVE)
This study aimed to assess mental health and excessive internet use among students at the Professional Secondary School of Education of the Faculty of Education Sciences at the National University of Altiplano in Puno, with participants having a mean age of 21.13 years (SD = 3.031), mostly between 20 and 23 years old (55.6%, n = 293) A quantitative methodology was used based on the 21-item self-reported Depression, Anxiety, and Stress Scale (DASS-21) and Pearson's correlation analysis. The results revealed positive and significant associations between internet use and levels of depression (r = 0.164; p < 0.001), anxiety (r = 0.128; p < 0.01), and stress (r = 0.185; p < 0.001), although of modest magnitude. In conclusion, increased time or intensity of internet use could contribute to increased negative emotional burden, possibly mediated by factors such as prolonged exposure to social media.